Comparative Hydrogen Production Routes via Steam Methane Reforming and Chemical Looping Reforming of Natural Gas as Feedstock - Mohd Yunus S.; Yusup S.; Johari S.S.; Mohd Afandi N.; Manap A.; Mohamed H. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Hydrogen production is essential in the transition to sustainable energy. This study examines two hydrogen production routes, steam methane reforming (SMR) and chemical looping reforming (CLR), both using raw natural gas as feedstock. SMR, the most commonly used industrial process, involves reacting methane with steam to produce hydrogen, carbon monoxide, and carbon dioxide. In contrast, CLR uses a metal oxide as an oxygen carrier to facilitate hydrogen production without generating additional carbon dioxide. Simulations conducted using Aspen HYSYS analyzed each method?s performance and energy consumption. The results show that SMR achieved 99.98% hydrogen purity, whereas CLR produced 99.97% purity. An energy analysis revealed that CLR requires 31% less energy than SMR, likely due to the absence of low- and high-temperature water?gas shift units. Overall, the findings suggest that CLR offers substantial advantages over SMR, including lower energy consumption and the production of cleaner hydrogen, free from carbon dioxide generated during the water?gas shift process. ? 2024 by the authors.